Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Mito Energi Indonesia - Suyade Hariyani; Rosmayani Rosmayani (SYNERGY: Jurnal Bisnis dan Manajemen, 2025)
This study aims to determine and analyze the effect of work discipline on employee performance at PT Mito Energi Indonesia. High work discipline has a significant impact on employee performance and organizational success. Using the type of research with a quantitative method approach. The population in this study included all employees who worked at PT Mito Energi Indonesia. The sample in this study consisted of 40 respondents using saturated sampling technique (census). Data collection was carried out through interviews, observations, and distributing questionnaires to all respondents. The analysis techniques used include validity test, reliability test, simple regression analysis, t test, coefficient of determination test, and statistical hypothesis testing. The results of this study indicate that the Work Discipline variable, with indicators such as accuracy in coming to work, accuracy in leaving time, compliance with applicable regulations, use of work uniforms, and responsibility in doing tasks, received responses from respondents in the Good category. While in the Employee Performance variable, which is measured through indicators of quality, quantity, and timeliness, the results of responses from respondents are also in the Good category. The results of the simple linear regression analysis show that Work Discipline has a significant relationship to Employee Performance.